Analisis Faktor Yang Mempengaruhi Kesediaan Ibu Hamil dalam Melakukan Vaksinasi COVID-19 Booster di Wilayah Kerja Puskesmas Balongpanggang Kabupaten Gresik - Mita Kusumawardani; Ivon Diah Wittiarika; Budi Prasetyo (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The coverage of the COVID-19 Booster vaccination for pregnant women is still very low, this is because there are still many pregnant women who experience doubts about making a decision to vaccinate. Pregnant women found that Booster doses were associated with higher maternal antibody levels and thus reduced risk for severe COVID-19 related outcomes, as well as a stronger degree of protection for the baby than mothers who only received the primary dose (1st dose and 2nd dose). The purpose of this study was to determine the factors associated with the willingness of pregnant women to carry out the COVID-19 Booster vaccination. This research is a quantitative research with correlation analytic method. The population in this study were pregnant women who were recorded in the PWS KIA K1 data for pregnant women at the Balongpanggang Gresik Health Center as many as 120 respondents, a sample of 55 samples. Sampling used a purposive sampling method by distributing questionnaires online via Google forms and offline using a paper-based-test technique. The results of the study showed that the willingness of pregnant women to carry out the COVID-19 Booster vaccination was 80%. Bivariate analysis in this study used Chi square, Fisher and Kruskal-wallis statistical tests. There is a relationship between education, knowledge and attitudes with the willingness of pregnant women to carry out the COVID-19 Booster vaccination in the working area of the Balongpanggang Health Center, Gresik Regency in 2023. The role of midwives, the community and the government is very much needed in efforts to fulfill the coverage of the COVID-19 Booster vaccination, especially in pregnant women who are a vulnerable population during a pandemic. An approach with the right health promotion strategy is expected to be able to help achieve the target of vaccination coverage.